Activation of liver X receptor/retinoid X receptor pathway ameliorates liver disease in Atp7B−/− (Wilson disease) mice. Issue 6 (22nd February 2016) - Hamilton, James P.; Koganti, Lahari; Muchenditsi, Abigael; Pendyala, Venkata S.; Huso, David; Hankin, Joseph; Murphy, Robert C.; Huster, Dominik; Merle, Uta; Mangels, Christopher; Yang, Nan; Potter, James J.; et al.
Abstract : Wilson disease (WD) is a hepatoneurological disorder caused by mutations in the copper‐transporter, ATP7B. Copper accumulation in the liver is a hallmark of WD. Current therapy is based on copper chelation, which decreases the manifestations of liver disease, but often worsens neurological symptoms. We demonstrate that in Atp7b −/− mice, an animal model of WD, liver function can be significantly improved without copper chelation. Analysis of transcriptional and metabolic changes in samples from WD patients and Atp7b −/− mice identified dysregulation of nuclear receptors (NRs), especially the liver X receptor (LXR)/retinoid X receptor heterodimer, as an important event in WD pathogenesis. Treating Atp7b −/− mice with the LXR agonist, T0901317, ameliorated disease manifestations despite significant copper overload. Genetic markers of liver fibrosis and inflammatory cytokines were significantly decreased, lipid profiles normalized, and liver function and histology were improved. Conclusions: The results demonstrate the major role of an altered NR function in the pathogenesis of WD and suggest that modulation of NR activity should be explored as a supplementary approach to improving liver function in WD. (Hepatology 2016;63:1828‐1841)